2007
DOI: 10.1111/j.1467-9280.2007.01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Planning to Reach for an Object Changes How the Reacher Perceives It

Abstract: Three experiments assessed the influence of the Ebbinghaus illusion on size judgments that preceded verbal, grasp, or touch responses. Prior studies have found reduced effects of the illusion for the grip-scaling component of grasping, and these findings are commonly interpreted as evidence that different visual systems are employed for perceptual judgment and visually guided action. In the current experiments, the magnitude of the illusion was reduced by comparable amounts for grasping and for judgments that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 26 publications
(36 reference statements)
5
57
0
Order By: Relevance
“…Intention also influences performance in visual-search tasks: when searching for a target amongst similarly oriented objects and similarly colored objects, participants made fewer initial saccades to objects of an incorrect orientation when intending to grasp than when intending to point (Bekkering and Neggers 2002). Also, intention to grasp a disc surrounded by smaller or larger circles, a task that is immune to visual illusions (eg Aglioti et al 1995;but see also Franz 2001), reduced the perceptual size of the Ebbinghaus illusion (Vishton et al 2007). In addition, concurrent and recently performed actions also influence perception.…”
Section: Discussionmentioning
confidence: 99%
“…Intention also influences performance in visual-search tasks: when searching for a target amongst similarly oriented objects and similarly colored objects, participants made fewer initial saccades to objects of an incorrect orientation when intending to grasp than when intending to point (Bekkering and Neggers 2002). Also, intention to grasp a disc surrounded by smaller or larger circles, a task that is immune to visual illusions (eg Aglioti et al 1995;but see also Franz 2001), reduced the perceptual size of the Ebbinghaus illusion (Vishton et al 2007). In addition, concurrent and recently performed actions also influence perception.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the actions we perform with our hands can influence how we see (e.g., Bekkering & Neggers, 2002;Fagioli, Hommel, & Schubotz, 2007;Vishton et al, 2007;Wohlschläger, 2000) and how we perform complex visual transformations like mental rotations (e.g., Wexler, Kosslyn, & Berthoz, 1998;Wohlschläger & Wohlschläger, 1998). These studies have revealed an intimate relationship between perception and actionin particular, the capacity for the latter to affect the former.…”
mentioning
confidence: 99%
“…It is well established that our actions are strongly guided by visual perception: Activities such as reaching, grasping, and pointing to objects are performed more accurately and faster when they occur within our visual field and, in particular, when presented within the current focus of our visual attention (e.g., Adam, Buetti, & Kerzel, 2012b;Castiello, 1999;Ma-Wyatt & McKee, 2007). Effects of action on visual perception, in turn, are more subtle and have only recently been studied (e.g., Bekkering & Neggers, 2002;Fagioli, Hommel, & Schubotz, 2007;Vishton et al, 2007;Wohlschläger, 2000). Emerging from this research is growing evidence that visual attentional mechanisms are affected by concurrent action planning (Baldauf & Deubel, 2008;Baldauf, Wolf, & Deubel, 2006;Fischer & Hoellen, 2004) and the position of our hands (Abrams, Davoli, Du, Knapp, & Paull, 2008;Reed, Betz, Garza, & Roberts, 2010;Reed, Grubb, & Steele, 2006; see also Adam et al, 2008).…”
mentioning
confidence: 99%